Transcriptome Profile During Rabies Virus Infection: Identification of Human CXCL16 as a Potential New Viral Target - Feige, Lena; Sáenz-de-Santa-María, Inés; Regnault, Beatrice; Lavenir, Rachel; Lepelletier, Anthony; Halacu, Ala; Rajerison, Randrianasolo; Diop, Sylvie; Nareth, Chhor; Reynes, Jean-Marc; Buchy, Philippe; Bourhy, Hervé; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Rabies virus (RABV), the causative agent for rabies disease is still presenting a major public health concern causing approximately 60,000 deaths annually. This neurotropic virus (genus Lyssavirus, family Rhabdoviridae) induces an acute and almost always fatal form of encephalomyelitis in humans. Despite the lethal consequences associated with clinical symptoms of rabies, RABV limits neuro-inflammation without causing major histopathological lesions in humans. Nevertheless, information about the mechanisms of infection and cellular response in the central nervous system (CNS) remain scarce. Here, we investigated the expression of inflammatory genes involved in immune response to RABV (dog-adapted strain Tha) in mice, the most common animal model used to study rabies. To better elucidate the pathophysiological mechanisms during natural RABV infection, we compared the inflammatory transcriptome profile observed at the late stage of infection in the mouse brain (cortex and brain stem/cerebellum) with the ortholog gene expression in post-mortem brain biopsies of rabid patients. Our data indicate that the inflammatory response associated with rabies is more pronounced in the murine brain compared to the human brain. In contrast to murine transcription profiles, we identified CXC motif chemokine ligand 16 (CXCL16) as the only significant differentially expressed gene in post-mortem brains of rabid patients. This result was confirmed in vitro, in which Tha suppressed interferon alpha (IFN-α)-induced CXCL16 expression in human CNS cell lines but induced CXCL16 expression in IFN-α-stimulated murine astrocytes. We hypothesize that RABV-induced modulation of the CXCL16 pathway in the brain possibly affects neurotransmission, natural killer (NK) and T cell recruitment and activation. Overall, we show species-specific differences in the inflammatory response of the brain, highlighted the importance of understanding the potential limitations of extrapolating data from animal models to human.